Drug-resistance in doxorubicin-resistant FL5.12 hematopoietic cells: elevated MDR1, drug efflux and side-population positive and decreased BCL2-family member expression - Steelman, Linda S.; Abrams, Stephen L.; Ruvolo, Peter; Ruvolo, Vivian; Cocco, Lucio; Ratti, Stefano; Martelli, Alberto M.; Neri, Luca M.; Candido, Saverio; Libra, Massimo; McCubrey, James A. (My University, 2017)
Chemotherapeutic drug treatment can result in the emergence of drug-resistant cells. By culturing an interleukin-3 (IL-3)-dependent cell line, FL5.12 cells in the presence of the chemotherapeutic drug doxorubicin, we isolated FL/Doxo cells which are multi-drug resistant. Increased levels of drug efflux were detected in FL/Doxo cells which could be inhibited by the MDR1 inhibitor verapamil but not by the MRP1 inhibitor MK571. The effects of TP53 and MEK1 were examined by infection of FL/ Doxo cells with retroviruses encoding either a dominant negative TP-53 gene (FL/ Doxo+ TP53 (DN) or a constitutively-activated MEK-1 gene (FL/Doxo + MEK1 (CA). Elevated MDR1 but not MRP1 mRNA transcripts were detected by quantitative RT-PCR in the drug-resistant cells while transcripts encoding anti-apoptotic genes such as: BCL2, BCLXL and MCL1 were observed at higher levels in the drug-sensitive FL5.12 cells. The percentage of cells that were side-population positive was increased in the drug-resistant cells compared to the parental line. Drug-resistance and side- positive population cells have been associated with cancer stem cells (CSC). Our studies suggest mechanisms which could allow the targeting of these molecules to prevent drug-resistance.